(untitled) (Global Journal of Human-Social Science, 2015)
Archaeotourism can take place in two main forms i on site or locations of discoveries and ii assembling the discoveries into museums or exhibitions Given that the first option in Kosovo has not proven viable a marketing strategy went on to be explored for the latter in broad terms by taking into account Bronze Age artifacts with engravings from the sacred geometry discovered by the Author of this paper during 2013-14 which were the work of ancient Illyrians Yet the results suggesta third alternative of archaeotourism development and that is the interest by respective foreign scholars institutions and foundations by using Long Tail marketing approach The paper interprets some astrological metaphors of sacred geometry in literature review but draws conclusions from archeological discoveries